2021 IEEE International Conference on Communications Workshops (ICC Workshops) 2021
DOI: 10.1109/iccworkshops50388.2021.9473842
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Intelligent Surface-Assisted Ambient Backscatter Communications – Experimental Assessment

Abstract: Sixth generation (6G) mobile networks may include new passive technologies, such as ambient backscatter communication or the use of reconfigurable intelligent surfaces, to avoid the emission of waves and the corresponding energy consumption. On the one hand, a reconfigurable intelligent surface improves the network performance by adding electronically controlled reflected paths in the radio propagation channel. On the other hand, in an ambient backscatter system, a device, named tag, communicates towards a rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…12, the RIS-assisted backscatter system achieves high spectrum efficiency for smaller distance between the transmitter and RIS. Furthermore, the authors in [82] experimentally demonstrated the improvement in the performance of backscatter communications with the aid of RIS.…”
Section: E Ris-assisted Iot Networkmentioning
confidence: 99%
“…12, the RIS-assisted backscatter system achieves high spectrum efficiency for smaller distance between the transmitter and RIS. Furthermore, the authors in [82] experimentally demonstrated the improvement in the performance of backscatter communications with the aid of RIS.…”
Section: E Ris-assisted Iot Networkmentioning
confidence: 99%
“…1. Other applications include the design of multi-stream multi-antenna transmitters with a single radio frequency chain (often called holographic surfaces and holographic MIMO) [24] and reconfigurable ambient backscatterers [25]. In general terms, an RIS is a candidate future wireless technology for controlling and shaping the electromagnetic waves in a dynamic and goal-oriented way, possibly turning the wireless environment into a service, and for realizing new transceiver designs and network elements at a lower complexity and power consumption.…”
Section: B Reconfigurable Intelligent Surfacesmentioning
confidence: 99%
“…The analytical formulation in (25) is not only analytically convenient, as it will be apparent next, but it has a useful physical interpretation. The function Φ(r Rx , r, r Tx ) corresponds to the phase shift that needs to be applied by the RIS, based on the geometrical optics approximation, in order to steer (reradiate) an electromagnetic wave the impinges upon S from the direction identified by k i (r Tx ) towards the direction identified by k r (r Rx ) [2].…”
Section: A Electromagnetically Consistent Modeling Of Rissmentioning
confidence: 99%
See 2 more Smart Citations